In vitro antibacterial activity of electrolytic silver nanoparticle against Staphylococcus aureus - Suparno, Suparno; Grace, Deby; Aziz, Khafid Nur; Brams, Dwandaru Wipsar Sunu; Lestari, Eka Sentia Ayu (Edelweiss Applied Science and Technology, 2024)
This paper reports a research project aimed at uncovering the antibacterial activity of electrolytic silver nanoparticles (ESN) against Staphylococcus aureus (S. aureus) with a focus on efficacy and power to prevent resistance. ESN is produced by electrolysis method. The silver content in the solution was characterized with a UV-visible spectrophotometer and the particle size was determined using dynamic light scattering (DLS). The antibacterial activity of silver nanoparticles was assessed using the Kirby-Bauer method. UV visible spectrometer measurements show an absorption wavelength peak of 414nm indicating that the solution contains silver atoms. The DLS measurement results show that the average ESN size is 93nm, the polydispersity index is 0.1579, and the size distribution is a single modal distribution graph showing small broadening. Raw data showed that chloramphenicol produced significantly higher efficacy than ESN. However, they are measured in different units (chloramphenicol in % and ESN in ppm). Analysis using a calibration curve shows that at the same concentration ESN 5% produces almost 85 times the efficacy compared to chloramphenicol 5%. Data also showed that S. aureus developed resistance to chloramphenicol after 42 hours. In contrast, it did not show resistance to ESN at all concentrations until the last observation at 48 hours indicating the power of ESN to prevent S aureus resistance. These two findings show that ESN has extraordinary potential as a raw material for future antibacterial agents.